On the behavior of a granular soil deposit subjected to horizontal vibration. A discrete element modeling - Derbane, Said; Mansouri, Mouloud; Messast, Salah; El Malki Alaoui, Aboulghit (Comptes Rendus. Mécanique)
This paper presents an analysis of the behavior of a non-cohesive granular material deposit excited at its base by a horizontal harmonic vibration. The analysis is carried out numerically by means of a 2D discrete element model. The performed simulations highlighted some aspects of vibration behavior in non-cohesive deposits, such as the shape of the vertical profile of the displacement, notably in the case of large displacements. The analysis particularly focused on the amplification of the movement at the free surface of the deposit, as well as its dependence on some parameters such as the excitation frequency and the excitation amplitude of the deposit confinement. The obtained results showed that the behavior of the deposit following the change in the excitation frequency is similar to the case of an elastic deposit excited by a harmonic displacement at the base, i.e. the Dynamic Amplification Factor (DAF) initially increases with the frequency increase, it reaches a peak of resonance then it decreases. The resonance frequency estimated from this analysis is close to the fundamental frequency for low excitation amplitudes, but becomes smaller as the excitation amplitude increases. On the other hand, for a fixed frequency, increasing the amplitude of the excitation induces greater amplification. It has been shown that this increase results from the degradation of the shear modulus due to the increase in the level of involved shear strain. Therefore, unlike elastic deposits, for non-cohesive granular deposits, increasing strain leads to a degradation of the shear modulus, resulting in a downward shift of the resonance frequency and can induce a significant increase in amplification. The confinement of the deposit is achieved by increasing the gravitational acceleration; it has been shown that increased confinement makes the deposit stiffer, and therefore reduces the amplification of the introduced movement.